The criminal protection of securities markets through the extraterritoriality of the jurisdiction: An approximation from the US model - Gimeno Beviá, Jordi (2019)
Stock markets play a critical role in the economy of the States, because they are the door of the input of capital and investment into a country. Their alteration through corrupt practices by companies may cause very serious damage both in the economy and in society. Consequently, markets must be regulated for, likewise, be protected. However, the application of rules and penal sanctions to foreign companies may result to problems of jurisdiction. In this sense, the American influence in the regulation and protection of the markets has been decisive and crucial in regulating European and Spanish laws and practices.